Evaluating heat and drought resilience in ancient Indian Dwarf wheat Triticum sphaerococcum Percival using stress tolerance indices - Kiran B. Gaikwad; Amit Kumar Mazumder; Manjeet Kumar; Akash Singh; Rihan Ansari; Nasreen Saifi; Monika A. Joshi; Prashanth Babu; V. K. Vikas; Sanjay Kumar Singh; Rajbir Yadav (Scientific Reports)
Abstract This study is the first to characterize the ancient wheat landrace Triticum sphaerococcum for drought and heat tolerance indices. A total of 116 T. sphaerococcum accessions and 6 bread wheat cultivars were evaluated under terminal heat (late sowing) and drought (restricted irrigation) stress during the 2021–22 (CS1) and 2022–23 (CS2) cropping seasons. Significant genotypic variation for stress indices was observed. T. sphaerococcum exhibited smaller yield declines under stress compared to bread wheat. In CS1, 57% of the accessions showed drought tolerance, and 63% exhibited heat tolerance. In CS2, 30 out of 45 accessions displayed tolerance to drought (SSI_D: 0.29–0.99), and 24 accessions showed tolerance to heat (SSI_H: 0.50–0.99). Correlation analysis revealed a negative correlation between the stress susceptibility indices (SSI, SSPI) and grain yield under stress, while yield index (YI), mean productivity (MP), geometric mean (GMP), harmonic mean (HM), and mean relative performance (MRP) showed a positive correlation. Using principal component, biplot, and cluster analyses, it was found that accessions TS49 and TS27 did best in drought stress and TS49, TS61, and PAUTS16 did best in heat stress. These ancient wheat accessions represent valuable genetic resources for breeding stress-tolerant wheat cultivars and enhancing genetic diversity.